Synthesis of Bi-based superconductor by microwave-assisted hydrothermal method - Lima, R. G. [UNESP]; Rodrigues, V. D. [UNESP]; Carvalho, C. L. [UNESP]; Teixeira, S. R. [UNESP]; Souza, A. E. [UNESP]; Zadorosny, R. [UNESP] (Iop Publishing Ltd, 2014)
In this work we studied the synthesis of BSCCO-2212 superconducting phase associating a quite similar method developed by Pechini with the microwave-assisted hydrothermal method. To study the influence of the microwaves on the properties of BSCCO system, we synthesized two samples by such method. For one sample we used carbonates and for the other one we used nitrates as chemical reagents. We also produced a reference sample just using carbonates by Pechini's method to compare their morphological and superconducting properties. The structural properties of the samples were analyzed by scanning electron microscopy and X-ray diffraction. The Bi-2212 phase is predominant in all samples and despites the nitrates-like sample has a broader distribution of grain size in comparison with the reference sample, its magnetic behaviour is closer to that presented by the reference one.